Shamans in Asia - Chilson, Clark, 1967-; Knecht, Peter, 1937- (London ; New York : RoutledgeCurzon, 2003)
Shamans are a central feature of many local religions throughout Asia. This title introduces the activities, worldviews, and lives of shamans in Siberia, China, Korea, Japan, Bangladesh and Pakistan.
Aspects of shamanism : an introduction / Peter Knecht -- The social significance of the shaman among the Chinese Reindeer-Evenki / F. Georg Heyne -- Shamanism in Bangladesh / Anwarul Karim -- A Hmong shaman's séance / Jean Mottin -- Chaesu kut : a Korean shamanistic performance / John A. Grim -- Miyako theology : shamans' interpretation of traditional beliefs / Takiguchi Naoko -- Liminal experiences of Miyako shamans : reading a shaman's diary / Takiguchi Naoko.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050, 082
Keywords: Shamanism -- Asia; BODY, MIND & SPIRIT -- Spirituality -- Shamanism; Shamanism; Asia; Electronic books